Treatment of carotid cavernous fistulae or cavernous aneurysms associated with a persistent trigeminal artery: report of three cases. - Debrun, G M; Davis, K R; Nauta, H J; Heros, R E; Ahn, H S (American Journal of Neuroradiology, 1988)
One case of traumatic carotid cavernous fistula and two cases of cavernous aneurysm associated with a persistent trigeminal artery are reported. Since a significant rate of infarctions or hemorrhages in the vertebrobasilar territory is associated with PTA, we prefer to permanently occlude the PTA during treatment of a carotid cavernous fistula or a cavernous aneurysm if the trigeminal artery can be sacrificed without jeopardizing the basilar circulation. These three patients were cured without complications. The internal carotid artery could be preserved in only one case.